38 PSEUDOANEURYSM: A RARE AND OFTEN FATAL COMPLICATION OF MYOCARDIAL INFARCTION. (1st January 2006) - Atwal, P.; Jain, S.; Sinna, S.
Abstract : Background: Rupture of the left ventricular free wall is a life-threatening complication of acute myocardial infarction (MI), most likely to occur in older female patients days after a first Q-wave MI. A rare patient may develop a slow leak of blood into the pericardial space, producing a chamber or a false sac, referred to as pseudoaneurysm. The resulting hematoma is contained within fibrous pericardial adhesions or organized fibrotic clot and is connected to the left ventricle through a narrow neck. Clinical examination may reveal a low-pitched systolic and diastolic, to and fro, type of murmur, in and out of narrow neck. Two-dimensional Doppler echocardiogram and transesophageal echocardiogram (TEE) may help confirm the diagnosis. Case Report: A 73-year-old female with a history of atherosclerotic heart disease status post coronary artery bypass graft, aortic stenosis status post valvuloplasty, diabetes mellitus, hypertension, presented with retrosternal chest pain, dyspnea, and sweating. Diagnosis of acute ST-elevation MI was confirmed by the presence of cardiac markers (CPK, troponin) and ST-segment elevations on electrocardiogram and the patient was treated with thrombolytic therapy. The patient was asymptomatic, but echocardiogram done on day 5 revealed a large lateral wall pseudoaneurysm and the patient was immediately transferred for surgical repair. Teaching Point: Rupture of left ventricular free wall accounts for approximately 15% of deaths in acute MI. Thin-walled pseudoaneurysms are devoid of myocardial tissue and have a high risk of rupture and should be immediately repaired.